The Chelsea detective. Series 2 [videorecording (DVD)] - Fincham, Peter (Acorn, 2023)
London's richest borough hides a dark side that Chelsea local DI Max Arnold knows all too well. Killers lurk among the art galleries and luxury homes, and it's up to Max and new partner Layla Walsh to expose them.